NEAREST CONSEQUENCES OF HOLIATRY CHRONIC DIFFUSE CATARRHAL GINGIVITIS FOR CHILDREN - Tkachenko, P.I.; Lokhmatova, N.M.; Korotich, N.N. (World of Medicine and Biology, 2015)
The paper presents the findings of the holiatry of chronic diffuse catarrhal gingivitis in two groups of children, that were observed during a half-year period. Dental check-up was made in 6 months and comparison of the results in the groups of comparison mede evident that patients that were treated by the suggested methodology (the additional application of Decasan antiseptic in the comprehensive therapy) had the best rates of hygiene indexes and state of parodentium tissues. It is made by evidence that the suggested curative complex allows to get more positive and stable clinical results and attain 1,5 times reduced number of exacerbations during 6 months.
Keywords: chronic catarrhal gingivitis; to put; treatment